Study on the properties of gold nanoparticles as plasmonic sensing material for chlorothalonil detection - Razali, Nur Liyana (2020)
Chlorothalonil-based fungicide has been employed extensively to prevent various fungal diseases in plants to increase yield of crops. Conversely, over-usage of chlorothalonil can have adverse effects to human health and environment. An optical sensor implemented Localized Surface Plasmon Resonance (LSPR) phenomenon offers direct and simple detection method has been developed for chlorothalonil detection. In this study, a simple technique of seed-mediated growth method (SMGM) has been successfully performed to grow gold nanoparticles (GNPs) onto solid substrates. The process parameters; seeding time, growth time and effect of capping agent’s molecular weight were investigated to monitor the effect on nanoparticles formation. It was found that increasing the seeding time affect the surface density of GNPs. Furthermore, the investigation on growth time shows significant impact to the shape and size of nanoparticles with 2 hours growth time formed small particles whiles 5 hours and more produces bigger particles. Moreover, in this work, molecular weight (MW) of polyvinylpyrrolidone (PVP) as shape controlling agent was also investigated to observe the uniformity of nanoparticles. PVP 55,000 produced more uniform shape and size of gold nanoparticles compared to PVP 40,000. The prepared sample with 3 hours seeding time, 8 hours growth time and 55k MW of PVP produced highest surface density of GNPs which is 53.66 ± 1.23 %. This sample was further used as a sensing material in detection of chlorothalonil. The sensitivity of the sensor system is determined by measuring the change of peak position and intensity on t-SPR and lSPR band of GNPs in three mediums; air, deionized water and chlorothalonil solution. Chlorothalonil with 30 mM concentration (without GNPs) exhibits no significant peak and thus proven that GNPs is more suitable to be used as sensing material. Besides, GNPs shows good stability response in 600 seconds with fast response and recovery time during five cycles change of medium. As a conclusion, the GNPs was successfully synthesised and used as sensing material for chlorothalonil detection from 1mM to 40 mM.